1985
DOI: 10.1002/j.1537-2197.1985.tb05364.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Threadlike Structures and Other Morphological Characters in Jacqueshuberia Pollen (Leguminosae: Caesalpinioideae)

Abstract: Threadlike structures were observed on many pollen grains of Jacqueshuberia amplifoliola, J. purpurea, and J. quinquangulata of the Leguminosae/Caesalpinioideae. Each end was attached to the highly reticulate polar exine surface of different grains. The consistency of this observation, hence, the absence of free thread ends, is interpreted to mean that they should be considered as either exine bridges or exinial connections rather than viscin threads, although, most likely functionally homologous to viscin thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been suggested that the presence of pollen-connecting threads is a derived character, evolved as an adaptation to zoophilous pollination (Arroyo 1981, Ferguson 1987 and that the threads contribute significantly to efficient pollination (Cruden & Jensen 1979). In particular, Caesalpinia pulcheriima, like D. regia, is reported to be bird pollinated (Arroyo 1981), and Jacqueshuberia is pollinated exclusively by bats (Arroyo 1981, Polhill et al 1981Patel et al 1985).…”
mentioning
confidence: 96%
“…It has been suggested that the presence of pollen-connecting threads is a derived character, evolved as an adaptation to zoophilous pollination (Arroyo 1981, Ferguson 1987 and that the threads contribute significantly to efficient pollination (Cruden & Jensen 1979). In particular, Caesalpinia pulcheriima, like D. regia, is reported to be bird pollinated (Arroyo 1981), and Jacqueshuberia is pollinated exclusively by bats (Arroyo 1981, Polhill et al 1981Patel et al 1985).…”
mentioning
confidence: 96%